Evaluación de las transferencias del sector eléctrico. El caso de San Carlos y el Oriente Antioqueño (2015)
This paper present the result obtained in the research related the Eastern municipalities of Antioquia with special focus in the municipality of San Carlos about the transfer of the power sector delivered to them during the years between 2000-20012, for concept to the intensive use of natural resources of the region (water and earth) that the power company make in the regions with hydropower settlements. In conclusions, we observed a compensatory inequality in the municipalities studied due the criterion for delivering predominates transfers is the installed capacity and the watershed criterion above the reservoir criterion which is more closely related to the consumption of land, and is the most visible contribution of natural capital of the municipalities in hydroelectric settlements element.